2017
DOI: 10.1049/iet-wss.2017.0027
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficient policy selection in wireless sensor network using cross layer approach

Abstract: The authors have addressed the issue of energy saving in packet retransmission by reducing the packet loss in the first attempt. They have formulated the problem as Markov decision process and mapped the system into various states based on system dynamics like channel gain, buffer space, battery energy and harvested energy. In wireless sensor network, adaptive policy management is the best approach to work out with the variation of system states in a dynamically changing environment. The policies are defined r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…So energy efficient MAC protocol plays a vital role in lifetime of WSN. Time division multiple access (TDMA) and Code division multiple access (CDMA) are appropriate one to avoid energy consumption at link layer In the research work [14], it is found that sleep synchronization among nodes affects energy consumption. Since the listening time in the MAC layer has to influence in relay delay and delivery ratio, the degree of sleep coordination between nodes yields the corresponding power consumption.…”
Section: Mac Layermentioning
confidence: 99%
See 1 more Smart Citation
“…So energy efficient MAC protocol plays a vital role in lifetime of WSN. Time division multiple access (TDMA) and Code division multiple access (CDMA) are appropriate one to avoid energy consumption at link layer In the research work [14], it is found that sleep synchronization among nodes affects energy consumption. Since the listening time in the MAC layer has to influence in relay delay and delivery ratio, the degree of sleep coordination between nodes yields the corresponding power consumption.…”
Section: Mac Layermentioning
confidence: 99%
“…• In [14], to produce synchronic and dynamic adaptive listening scheme author jointly considers listening time in MAC layer and routing scheme in the network layer, along with the channel information from the physical layer. The forward delay and energy consumption are reduced due to the coordination between nodes in terms of their sleeping time.…”
Section: Possible Solution To Increase Energy Efficiency In Wsnmentioning
confidence: 99%
“…Let C g = c g = 0.5, C p = C g + c p = 0.5 + 0.2 = 0.7, C w = C p + c w = 0.7 + 0.25 = 0.95, X 10,8 = (1.1, 1.8, 3.5, 2.2, 0.1) which is the 8th solution of the 11th generation, P 8 = (2.5, 2.0, 1.2, 1.9, 5.0), and P gBest = (3.3, 2.8, 1.2, 4.5, 5.6). An example is shown below to explain how SSO is implemented to update X 10,8 to X 11,8 in Table 2. The lower bound l i , the upper-bound u i , and the value of ρ i for variable x 10,8,i are listed in the 2nd, 3rd and 7th row of Table 2, respectively.…”
Section: The Sso and An Examplementioning
confidence: 99%
“…Mekonnen et al [2] proposed a prototype of a WSN applied in a video surveillance system to optimize energy consumption. Trapasiya and Soni [11] addressed the goal of retransmission energy reduction in WSNs. Quang and Kim [12] proposed a gradient routing in an industrial WSN to optimize energy consumption.…”
mentioning
confidence: 99%
“…Xia Weichao [8] deeply analyzed the relationship between satisfying customer needs and supplier management and believed that category management should be based on category accounting, which is designed to meet consumer needs and manage suppliers' new management methods. Wu Zikai [9] emphasized the importance of category tactics.…”
Section: Introductionmentioning
confidence: 99%